Behavior And Hiv/Sti Seroprevalence Survey Among Migrant Labors, Their Wives And Other Women With Sti Syndromes In Kanchanpur - Bohara, MS; Dhungana, GP; Thakuri, BC (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2012)
Introduction: Migrant people were high risk group in acquiring HIV and others STI. Nepal is facing rapid increase in prevalence among high-risk groups such as sex workers, injection drug users and migrants. Western part of Nepal faces the same threat. The objective of the study is to measure HIV/STI status in-migrant labors, their wives and women with STD syndromes in Kanchanpur. Methodology: A cross-sectional analytical study was carried out in migrant labors, their wives and women with STD syndromes in year 2009 at Department of Microbiology, Siddhanath Science Campus, Mahendranagar, Kanchanpur. Results: Out of 208 migrant workers, wife/husband of migrant workers, children of migrant workers 18(8.5 %) were found HIV positive and 40 (19%) had different STI. The HIV acquiring is highly associated with STIs co- infected patients (p<0.01). Fifty-three (26%) respondents always used condom and 47 (23%) did not use. A large number 43(21%) had prostitute as sexual partner and majority of 130 (64%) were stricted to single sexual partner but 49 (24%) had 2 to 4 sexual partners and 24 (12%) had more than 4 sexual partners. Conclusion: It was found that migrant people were at high risk of acquiring HIV and other STIs. Male migrants may engage in having sexual relationship with multiple partners. Adult migrant had HIV infection. The HIV infection was signifi cantly associated with other STIs. DOI: http://dx.doi.org/10.3126/saarctb.v8i1.5886 SAARCTB 2011; 8(1): 9-14